2003
DOI: 10.1002/jcb.10589
|View full text |Cite
|
Sign up to set email alerts
|

Effect of overexpressing fibroblast growth factor 2 protein isoforms in osteoblastic ROS 17/2.8 cells

Abstract: Fibroblast growth factor-2 (FGF-2) is made by osteoblasts and modulates their function. There are high molecular weight (HMW) protein isoforms of FGF-2 that have nuclear localization sequences and a low molecular weight (LMW) 18 kDa FGF-2 protein that is exported from cells. Since FGF-2 is a trophic factor and potent mitogen for osteoblasts, the goal of this study was to utilize targeted overexpression of FGF-2 as a novel means of assessing different FGF-2 isoforms on osteoblastic cell viability and proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Transfection of FGF2 isoforms in an osteoblastic cell line showed that neutralizing FGF2 antibodies blocked cell growth in FGF2 LMW overexpressing cells but not in FGF2 HMW isoforms overexpressing cells, suggesting that the FGF2 HMW isoforms modulate cell growth and DNA synthesis by a mechanism independent of its cell surface receptors [29]. In cardiomyocytes, both LMW and HMW isoforms increase proliferation while FGF2 HMW overexpression significantly increased binucleation [30].…”
Section: Discussionmentioning
confidence: 97%
“…Transfection of FGF2 isoforms in an osteoblastic cell line showed that neutralizing FGF2 antibodies blocked cell growth in FGF2 LMW overexpressing cells but not in FGF2 HMW isoforms overexpressing cells, suggesting that the FGF2 HMW isoforms modulate cell growth and DNA synthesis by a mechanism independent of its cell surface receptors [29]. In cardiomyocytes, both LMW and HMW isoforms increase proliferation while FGF2 HMW overexpression significantly increased binucleation [30].…”
Section: Discussionmentioning
confidence: 97%
“…14, 24 Xiao and colleagues recently reported a bicistronic vector encoding for basic fibroblast growth factor (bFGF) along with the green fluorescent protein (GFP) reporter gene. 25 There is however, no information about 1 vector simultaneously encoding for 2 angiogenic growth factors to achieve therapeutic angiogenesis. Moreover, adenoviral vector administration triggers host inflammatory reactions and immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferative activity of HMW FGF2 has been well documented in NIH3T3 and A31 fibroblasts, adult bovine aortic endothelial (ABAE) cells, cardiac myocytes and ROS17/2.8 osteosarcoma cells [39, 4853]. In NIH3T3 cells, this proliferation also takes place in low-serum conditions [29, 49, 50].…”
Section: Cell and Tissue Phenotypes Modulated By Hmw Fgf2mentioning
confidence: 99%